12x+9y=7

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 12x from both sides of the equation.

9y=7-12x

Divide each term by 9 and simplify.

Divide each term in 9y=7-12x by 9.

9y9=79+-12×9

Cancel the common factor of 9.

Cancel the common factor.

9y9=79+-12×9

Divide y by 1.

y=79+-12×9

y=79+-12×9

Simplify 79+-12×9.

Simplify each term.

Cancel the common factor of -12 and 9.

Factor 3 out of -12x.

y=79+3(-4x)9

Cancel the common factors.

Factor 3 out of 9.

y=79+3(-4x)3(3)

Cancel the common factor.

y=79+3(-4x)3⋅3

Rewrite the expression.

y=79+-4×3

y=79+-4×3

y=79+-4×3

Move the negative in front of the fraction.

y=79-4×3

y=79-4×3

Reorder 79 and -4×3.

y=-4×3+79

y=-4×3+79

y=-4×3+79

Rewrite in slope-intercept form.

y=-43x+79

y=-43x+79

Using the slope-intercept form, the y-intercept is 79.

b=79

Find the Y-Intercept 12x+9y=7